2011
DOI: 10.1111/j.1600-0404.2010.01391.x
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous genetic variant of mitochondrial uncoupling protein 4 affects the occurrence of leukoaraiosis

Abstract: The present findings indirectly raise the possibility that a shift or imbalance in the finely regulated MMP may play a role in the development of LA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Accordingly, the expression of UCP4 has been found significantly reduced in brains of subjects affected by Alzheimer disease [91]. Moreover, it was found that CC genotype for rs10807344 of UCP4 gene, not found to be associated in the present study with the longevity phenotype, exerts a protective effect on the occurrence of multiple sclerosis and of leukoaraiosis, a vascular demyelinization of the white matter of the brain [92], [93]. Thus, it is likely that variants affecting the UCP4 function might have consequences on the aging of the nervous system, and then might have a potential impact on health and longevity.…”
Section: Discussionmentioning
confidence: 52%
“…Accordingly, the expression of UCP4 has been found significantly reduced in brains of subjects affected by Alzheimer disease [91]. Moreover, it was found that CC genotype for rs10807344 of UCP4 gene, not found to be associated in the present study with the longevity phenotype, exerts a protective effect on the occurrence of multiple sclerosis and of leukoaraiosis, a vascular demyelinization of the white matter of the brain [92], [93]. Thus, it is likely that variants affecting the UCP4 function might have consequences on the aging of the nervous system, and then might have a potential impact on health and longevity.…”
Section: Discussionmentioning
confidence: 52%
“…However, in keeping with the hypothesis that ucp4 and ucp5 may not regulate canonical uncoupling, no similar associations have been reported for ucp4 and ucp5 (29). Interestingly, single nucleotide polymorphisms (rs10807344 CC) in ucp4 have been linked to protection against both multiple sclerosis susceptibility and brain leukoaraiosis (30,31), and others link the same ucp4 mutation to increased schizophrenia incidence (32). We found that mutant ucp4 nematodes exhibited decreased respiration and increased levels of stored triglycerides and several fatty acids species when compared with N2.…”
Section: Discussionmentioning
confidence: 74%
“…This finding suggests that impaired mitochondrial physiology is sufficient to generate a delay in OPC differentiation and implies a possible explanation for the observed association between genetic variants of UCPs in two types of demyelinating disorders: MS and leukoaraiosis. [41][42][43][44] In addition, a concomitant increase in ROS would worsen the impairment of differentiation, explaining the correlation between increased ROS levels and the severity of the demyelinating disorder. 38,39 On the basis of these results, the cells exposed to TNF-a were expected to exhibit metabolic impairments.…”
Section: Discussionmentioning
confidence: 99%